The Analysis of Teacher Candidates’ Self-Sufficiency about Their Teaching Abilities at Different Departments - VAR, Levent (Asian Journal of Education and Training, 2018)
Self-sufficiency is an individual’s perception of his/her ability and skills to overcome various possible situations. This study aims to analyze self-sufficiency about their teaching abilities of teacher candidates studying at different departments at University of Kırşehir Ahi Evran. The research groups consists of 244 teacher candidates who study classroom teaching, mathematics teaching and Turkish language teaching at Faculty of Education and physical education and sports teaching, coaching education and sports management at School of Physical Education and Sports and attend a teaching formation program. Mean age of the students participating in the study is x̄=22.52. SPSS 22.0 package program for Windows was used for descriptive and One-way ANOVA analysis, and the level of significance was taken as 0.05. When self-sufficiency points of different departments are analyzed, it can be observed that students of physical education had the highest point as 93.09±24.07, while students of classroom teaching had the lowest point as 58.64±14.03.